P409 Long-term safety and effectiveness of adalimumab in 462 patients with intestinal Behçet's disease: Results from a real-world observational study. (16th January 2018) - Suzuki, Y; Hagiwara, T; Kobayashi, M; Morita, K; Shimamoto, T; Hibi, T
Abstract: Background: Safety and effectiveness of adalimumab (ADA), an anti-tumour necrosis factor-α antibody, was demonstrated in a small phase 3 trial in Japanese patients with intestinal Behçet's disease (BD). We conducted an observational study to evaluate the real-world safety and effectiveness of ADA in intestinal BD. Methods: This prospective, all-cases, and post-marketing study was conducted between 2013 and 2017 at 254 centres in Japan (NCT01960790). Patients with intestinal BD who had an inadequate response to their current treatment were included. Observation period was predefined based on the initial treatment stage of the patients. ADA was administered subcutaneously at an initial dose of 160 mg followed by 80 mg at 2 weeks and then 40 mg every 2 weeks. Primary endpoint was incidence of adverse drug reactions (ADRs). Effectiveness endpoints included global improvement scale (rated effective/markedly effective/ineffective by physician) and change in C-reactive protein (CRP) levels from baseline (as observed). Results: Of 473 registered patients, 462 and 383 included in the safety (Table 1) and effectiveness cohort were followed up for mean ± standard deviation (SD) of 515.3 ± 322.2 and 579.5 ± 307.9 days, , respectively. The observation period in the safety population was 52 ( n = 146), 104 ( n = 223) and 156 weeks ( n = 93). ADRs and serious ADRs were reported in 120 (25.97%) and 51 (11.04%) patients, , respectively (Table 2). Two of three patients who suffered from tuberculosis (TB) during the study were screened positive for TB at baseline and had initiated anti-tubercular treatment before starting ADA. No cases of de novo or reactivation of hepatitis B were reported. Incidence of ADRs was significantly higher in patients with comorbidities ( p < 0.0001), a past medical history ( p = 0.0132), in those taking concomitant oral corticosteroids ( p < 0.0001) and not self-administering ADA ( p = 0.0257). In the effectiveness cohort, 324 (84.6%) patients had a global improvement rating of "effective" (156 [40.7%]) or "markedly effective" (168 [43.9%]) at study end. Mean ± SD CRP levels decreased from baseline (1.96 ± 3.36; n = 324) to Weeks 24 (0.58 ± 1.59; n = 208), 52 (0.60 ± 1.53; n = 186), 104 (0.44 ± 1.19; n = 142), and 156 (0.25 ± 0.62; n = 37). Conclusions: The safety and effectiveness of ADA treatment in routine clinical practice was confirmed in this large population with intestinal BD. No new safety concerns were identified.